Teacher's Pedagogic Competence in Teaching English: An Analysis Study - Febriani; Gatot Subroto; Dewi Murni (Juliet, 2022)
The teaching and learning process is changed from offline learning became online learning due to Covid-19 outbreaks. The aimed of this study was to describe how is the pedagogical competence of English teachers at SMPN 7 Tanjungpinang. This research used qualitative research method which means that the researcher describes the result of the data about teacher’s pedagogical competence consists of understanding of the students, designing of the material, developing students’ potential and evaluation. Observation and interview were used as the instruments of this research. The result showed that the pedagogical competence of English teachers in online learning is on good categories with keep regard and adjust to the needs of students during online learning. Moreover, the teachers must always improve their pedagogical competence especially in online learning. Key Words: Pedagogic Competence, Online Learning, Google Classroom